2021
DOI: 10.26464/epp2021042
|View full text |Cite
|
Sign up to set email alerts
|

A measure of ionospheric irregularities: zonal velocity and its implications for L-band scintillation at low-latitudes

Abstract: We estimated zonal drift velocity of small-scale ionospheric irregularities by means of spaced GNSS receivers technique in Brazil.q We validated our results against independent measurements and an empirical model. qWe found a very good correlation between zonal drift velocy of the small-scale irregularities and amplitude scintillation occurrence during post-sunset hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
(70 reference statements)
1
2
0
Order By: Relevance
“…As a consequence, the slope of each black line estimates the EPBs speed, which is reported in Figure 3c. The retrieved speed is positive, that is, EPBs drift eastward, and ranges between 30 and 90 m/s, in partial agreement with what reported by other works addressing plasma drift velocity measurements in the Brazilian EIA crest sector, but under different solar activity conditions and by means of different techniques (Cesaroni, et al, 2021b;Ledvina et al, 2004;Muella et al, 2009). Those works address the zonal drift velocity of the small-scale ionospheric irregularities embedded in the EPBs, while here the measurement is made by using an estimate based on large-scale TEC structures.…”
Section: Resultssupporting
confidence: 90%
“…As a consequence, the slope of each black line estimates the EPBs speed, which is reported in Figure 3c. The retrieved speed is positive, that is, EPBs drift eastward, and ranges between 30 and 90 m/s, in partial agreement with what reported by other works addressing plasma drift velocity measurements in the Brazilian EIA crest sector, but under different solar activity conditions and by means of different techniques (Cesaroni, et al, 2021b;Ledvina et al, 2004;Muella et al, 2009). Those works address the zonal drift velocity of the small-scale ionospheric irregularities embedded in the EPBs, while here the measurement is made by using an estimate based on large-scale TEC structures.…”
Section: Resultssupporting
confidence: 90%
“…Following this, in the current study, zonal drift velocity of irregularity is measured, from scintillation patches observed at S band of IRNSS (Indian Regional Navigation Satellite System) and L1 band of GNSS (GPS: Global Positioning System, GLONASS: Global Navigation Satellite System, Galileo), using spectral analysis method. Previously, zonal drift velocity of ionospheric plasma bubbles has been calculated, using spaced aerial measurements (Briggs et al., 1950), which is more conveniently applied with VHF (Very High Frequency : 30 to 300 MHz) systems (T. Das et al., 2014; Olwendo et al., 2013), closely spaced GPS receiver observations (Cesaroni et al., 2021; de Paula et al., 2002; Ji et al., 2011; Kil et al., 2000; Muella et al., 2009), incoherent scatter radar measurements (Fejer et al., 1981, 1985) and space‐based measurements from an imager in NASA‐IMAGE satellite (Immel et al., 2004). Observations of equatorial plasma bubble drift velocity using airglow OI630 nm all‐sky digital images have also been reported in comparison with model predictions (Arruda et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…An enhanced poleward wind associated with a passing-by brightness wave may have transported plasma to fill the airglow depletions, which finally evolved into brightness airglow structures. Cesaroni et al (2021) studied the zonal drift velocity of small-scale ionospheric irregularities at low latitude by applying the spacedreveiver technique to measurements collected during the period September 2013-February 2014 by two GNSS reveivers for scintillation monitoring installed along the magnetic parallel passing through Presidente Prudente (Brazil, magnetic latitude 12.8°S). They found that the hourly average of the velocity increased up to 135 m/s right after the local sunset and then smoothly decreased in the next hours, in agreement with independent estimations of the velocity made by the incoherent scatter radar at Jicamarca (magnetic latitude 0.1°N), and by the Boa Vista ionosonde (magnetic latitude 12.0°N).…”
mentioning
confidence: 99%